STRUKTUR EKONOMI, KESEMPATAN KERJA DAN KETIMPANGAN PENDAPATAN DI PROVINSI JAWA TENGAH - Suhartono, Suhartono (Jurnal Organisasi dan Manajemen, 2011)
The purpose of article is to analyze the potential economic sectors, opportunity job and disparity income in Central Java. The methods using Location Quotient (LQ), Shift Share and Inequality Index Williamson. The results of LQ analysis shows that threre are potential sectors to be developed in the province of Central Java. They are agriculture, livestock, forestry and fisheries, mining and quarrying, electricity, gas and water supply, communications and transport sector, financial sector, leasing and banking services and the services sector. Shift Share analysis results that in the cities in Central Java province has been a shift or change in the economic structure of the primary sector to tertiary sector. Meanwhile, the calculation of income inequality shows that income inequality between regions in Central Java province is very high, Recommendations addressed to the local government to implement economic development with more attention to aspects of equitable distribution of income.